The Effectiveness of Story Telling and Role Play in Teaching Speakingfor Students with High and Low Motivation - Mayasari, Adhe Risky; Faridi, Abdurrachman; Fitriati, Sri Wuli (English Education Journal, 2021)
Storytelling and role play as techniques of teaching have been studied and believed to be effective for teaching speaking. In speaking class, students’ interest and motivation are also improved as the impact of the techniques. The present research aims at explaining how significant the students’ achievement is taught by using storytelling and role-play as techniques of teaching speaking to the students with high and low levels of motivation. The design of this research was a quasi-experimental design with a 2x2 factorial design. This research was conducted on eleventh-grade students at MA Al-Hikmah Bandar Lampung as the research participants. Then, the writer analyzed the result from the questionnaire and speaking test using t-test and ANOVA. The results of this research showed that the value of sig. of techniques and motivation was 0.00. It meant that sig. the value was lower than 0.05. It can be concluded that there was a significant difference in the students’ achievement taught by storytelling technique and roleplay technique for students with high and low motivation. This research is expected to give a contribution to English teaching-learning such as giving appropriate techniques to teach speaking comprehension.